Dermoscopy of papillomatosis cutis lymphostatica: a report of two cases - Nowowiejska, Julia; Arias-Rodriguez, Camilo; Argenziano, Giuseppe; Brancaccio, Gabriella (Dermatology Review/Przegląd Dermatologiczny, 2024)
Papillomatosis cutis lymphostatica is a rare skin condition characterized by the presence of verrucous and papulo-nodular lesions on the lower limbs due to lymphatic stasis leading to chronic edema. Dermoscopy of papillomatosis cutis lymphostatica has been poorly defined. Two adult obese men presented with pink and flesh-colored papulo-nodular and papillomatous firm and exudative lesions, located on both legs. Lesions were covered with honey-colored crusts indicating bacterial superinfection. On dermoscopy examination, there were non-focused dotted vessels clustered in squares, resembling red rosettes, distributed within the whole lesion, in some cases with a glomerular aspect; in other lesions, vessels were separated by white lines resembling the inverse network. There were also shiny white structures – blotches and strands. Lesions had a pink structureless background. Besides the clinical picture, dermoscopy may support the diagnosis of papillomatosis cutis lymphostatica, especially in cases of atypical manifestations. Further reports on this matter will help to determine if these characteristics are typical of papillomatosis cutis lymphostatica.